Perencanaan Sumber Daya Manusia Dengan Metode ABK Kes Pada Petugas Rekam Medis Rumah Sakit di Surakarta - Agustyarum Pradiska Budi; Arifah Damayanti; Zahra Kirana Firdausi; Wella Niki Putri; Pingki Nofita (JURNAL KEPERAWATAN SISTHANA, 2019)
The WISN and ABK-Kes methods can be used to calculate the workload and staff requirements in the medical record unit. Medical record workers often catch several jobs without calculating the workload, so they feel a high workload. The purpose of this research is to analyze the need for medical personnel using the WISN and ABK-Kes methods. This study uses a type of qualitative research with a descriptive research design. The population in this study were all medical record officers. With eight medical record officers as samples. The results showed that based on calculations using the WISN and ABK-Kes methods, ten medical record officers were needed. So the proposed solution is to add expert medical record officers who are competent in their fields according to the calculation of the need for medical personnel according to the ABK-Kes method. This makes the medical record unit more reliable and ideal, because it is in accordance with PMK No. 33 of 2015 the addition of SDMK.